Transverse Eponychial Flap For Nail Lengthening And Fingertip Reconstruction - Manadhar, Krishna (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Fingertip injuries are frequented with loss of pulp and nail complex. Most reconstructive procedures provide either the soft tissue defect coverage or lengthen the nail. Methods: Patients included were more than 10 years of age with fingertip injury of Allen type III and IV with intact eponychium. Transverse Eponychial Flap was used to lengthen the nail lost as well as provide defect coverage. Paired t test, chi square test and Pearson correlation and Mann Whitney test were used for statistical analysis. Results: Seventeen digits were analyzed. The average lengthening of the nail achieved was 142.4%. The average nail length during follow up was 59.1% of contralateral, with average final nail lengthening achieved was 31%. Reconstruction with Transverse Eponychial flap alone was performed in 58.8% of digits. Four patients (23.52%) had complete near normal nail. Sixteen digits had satisfactory and higher results. With Transverse Eponychial Flap alone it was possible to completely cover 10 fingertips (58.8%), requiring local flaps or skin graft for the remaining cases. Obliquely orientated injuries (76.47%) were more likely to undergo the procedure. Conclusion: The flap significantly lengthens the nail, and provides satisfactory results. We recommend the use of this flap in defects with Allen type III and IV fingertip injuries.